CHRONIC DIARRHEAS IN PEDIATRIC PRACTICE: MODERN APPROACH TO DIAGNOSTICS - I.N. Zaharova; Yu.A. Dmitrieva ("Paediatrician" Publishers LLC, 2011)
(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 162-165)